Modification of oyster shell powder by humic acid for ammonium removal from aqueous solutions and nutrient retention in soil. Issue 6 (December 2021) - Lu, Mingyi; Shi, Xiaoshuang; Feng, Quan; Zhang, Mengdan; Guo, Yu; Dong, Xiaohuan; Guo, Rongbo
Abstract: Oyster shell (OS) can be used as absorbent, building material, catalysts and agricultural supplement due to the specific physicochemical properties. To add to the value of this wild raw material, a novel humic acid-modified oyster shell (HAOS) was prepared by introducing humic acid (HA) onto the OS surface through a solid phase grafting method. Thermogravimetric analysis (TGA), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and energy-dispersive X-ray (EDX) spectroscopy were performed to optimize the modification conditions. Batch adsorption experiments were designed to evaluate the effects of HA coating, pH, salinity, isotherm and kinetics on NH4 + adsorption. A soil column experiment was carried out to investigate the nitrogen release upon HAOS addition. The results showed that the adsorption capacity of HAOS for NH4 + increased by 43.5% compared with OS. The adsorption kinetics of NH4 + on HAOS could be explained by the pseudo-second-order kinetic model (R 2 = 0.9864), and the maximum adsorption amount calculated from the Langmuir adsorption model (R 2 = 0.9907) was approximately 56.1 mg g −1 . Moreover, 5% HAOS addition could prolong the release time of NH4 + and decrease the amount of NO3 - leaching from soil. The application of HAOS in the plant growth assay significantly increased the elongation and fresh weight of the test plants. Consequently, the novel HAOS had broad application prospects in ammonium treatment and soil fertility improvement. Graphical Abstract: ga1 Highlights: Develop a new humic acid-modified oyster shell by solid phase grafting. Humic acid-modified oyster shell showed a faster adsorption rate of NH4 + . Modified oyster shell increased the NH4 + adsorption capacity by 43.5%. Modified oyster shell application prolongs the release time of NH4 + in the soil. Soil NO3- retention was increased under 5% modified oyster shell additions.